2014
DOI: 10.1186/1471-2458-14-748
|View full text |Cite
|
Sign up to set email alerts
|

‘Red Ruby’: an interactive web-based intervention for lifestyle modification on metabolic syndrome: a study protocol for a randomized controlled trial

Abstract: BackgroundAlthough effectiveness of web-based interventions on lifestyle changes are recognized, the potential of such programs on metabolic syndrome has not been explored. We describe the protocol of a randomized controlled trial that aims to determine the feasibility, acceptability, usability, and effectiveness of interactive technology on lifestyle intervention in a population with metabolic syndrome.Methods/designThis is a two-arm randomized controlled trial. The study includes 160 participants (n = 80 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 77 publications
1
11
0
1
Order By: Relevance
“…This study was a cross-sectional investigation of 160 Iranian adults patients with metabolic syndrome living in Tehran; the details of this study has been reported elsewhere [11,12]. Briefly this was an internet-based life style modification interactive program, and we enrolled community-dwelling individuals from Jun 22 to August 22, 2012.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a cross-sectional investigation of 160 Iranian adults patients with metabolic syndrome living in Tehran; the details of this study has been reported elsewhere [11,12]. Briefly this was an internet-based life style modification interactive program, and we enrolled community-dwelling individuals from Jun 22 to August 22, 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study design have been submitted elsewhere. [ 33 34 ] Participants were recruited from an online registration website namely Healthy Heart Education ( http://www.Heartresearch.ir ). This website is designed to increase public's awareness about CVDs and MetS.…”
Section: Methodsmentioning
confidence: 99%
“…The Red Ruby was a randomized controlled trial conducted in Tehran, Iran. A detailed description of the method can be found elsewhere in a presentation of the study protocol [ 19 ]. Briefly, this study was designed to assess the effects of interactive web-based lifestyle intervention on metabolic syndrome.…”
Section: Methodsmentioning
confidence: 99%